Assessment of food safety knowledge, attitudes, and practices among street food vendors in Malaysia - Abdul Aziz , Nur Amelia Syakira; Kamarulzaman, Nitty Hirawaty; Abdul Hadi, Ahmad Hanis Izani (Hasanuddin University Food Science and Technology Study Program, 2024)
Street food in Malaysia is gaining popularity due to its competitive pricing and accessibility for consumers. However, unsanitary methods and processes have raised concerns about foodborne diseases, making it a major food safety concern. This study aims to: 1) investigate the levels of food safety knowledge, attitudes, and practices among street food vendors; 2) determine the associationbetween demographic characteristics and food safety practices; and 3) investigate the factors influencing food safety practices among these vendors. The study was conducted in the Klang Valley area, and a purposive samplingmethod was used to select 268 street food vendors. Descriptive, Chi-square, and logistic regression analyses were conducted to analyse the data. The findings reveal that most street food vendors possess adequate knowledge, favourable attitudes and follow food safety practices. Key factors influencing food safety practices included knowledge, attitudes, education level, type of stall, monthly revenue, food safety training, and typhoid injection. Most notably, monthly revenue emerged as a significant factor, where vendors with higher incomes were more likely to implement good food safety practices. Hence, authorities should offer incentives such as equipment procurement subsidies and microcredit schemes to street food vendors to empower them to overcome financial constraints and invest in necessary practices that ultimately lead to improved food safety standards